Has the time for first-line treatment with second generation tyrosine kinase inhibitors in patients with chronic myelogenous leukemia already come? Systematic review and meta-analysis - Ronit Gurion; Anat Gafter-Gvili; Liat Vidal; Avi Leader; Ron Ram; Adi Shacham-Abulafia; Mical Paul; Isaac Ben-Bassat; Ofer Shpilberg; Pia Raanani (Haematologica, 2012)
Second generation tyrosine kinase inhibitors have recently been introduced as first-line treatment for chronic phase chronic myelogenous leukemia. We aimed to evaluate the efficacy and safety of 2nd generation tyrosine kinase inhibitors versus imatinib as first-line treatment for these patients. We carried out a systematic review and meta-analysis of randomized controlled trials comparing 2nd generation tyrosine kinase inhibitors to imatinib as first-line treatment in chronic phase chronic myelogenous leukemia patients. Outcomes assessed were: complete cytogenetic response and major molecular response at 12, 18 and 24 months, all-cause mortality and progression to accelerated phase/blastic crisis at 12, 18 and 24 months, and chronic myelogenous leukemia related mortality and toxicity at last follow up. Relative risks were estimated and pooled using a fixed effect model. Our search yielded four trials including 2,120 patients. At 12 months, treatment with 2nd generation tyrosine kinase inhibitors significantly improved both complete cytogenetic response and major molecular response (relative risk 1.16, 95% CI: 1.09-1.23, and 1.68, 95% CI: 1.48-1.91, respectively). While major molecular response was improved at all time points, complete cytogenetic response improved at 18 months but not at 24 months. Importantly, rate of progression to accelerated phase/blastic crisis was significantly lower with the newer tyrosine kinase inhibitors throughout all time points. Second generation tyrosine kinase inhibitors improved chronic myelogenous leukemia related mortality without a statistically significant difference in all-cause mortality at 12, 18 and 24 months. We conclude that 2nd generation tyrosine kinase inhibitors can be added safely to the first-line treatment armamentarium of chronic phase chronic myelogenous leukemia patients. Although an advantage is suggested by surrogate parameters, longer follow up is necessary to see if this translates into superior overall survival.